Effect of NA-CMC Gelling Agent on Physical Properties of Hand Sanitizer with Basil Essential Oil (Ocimum sanctum L) - Lidia Putama Mursal, Iin; Hari Kusumawati, Anggun; Hartianti Puspasari, Devi; Puspitasari, Mawarnie (International Journal of Psychosocial Rehabilitation, 2020)
Hand sanitizers were effective and inexpensive product that can reduce of microorganims on the skin. Many hand sanitizer have contents up to 60%-95% ethanol and isopropyl alcohol, but using alcohol in hand sanitizer can cause health risks effect. The leaves of basil oil (Ocimum sanctum L.) can be used as an active ingredient for hand sanitizers because it has an antibacterial activity. The aim of this work was to determine the effects of gelling agent Na-CMC on physical properties of formulation gel hand sanitizer. The concentration that used for the Na-CMC gelling agent are 3%; 3,5%; 4%. The test of physical properties includes organoleptic, homogeneity, pH, viscosity, dispersive ability, and adhesion The results of this research on the physical properties gel hand sanitizer of basil essensial oil, showed that the increasing of gelling agent consentrasion, makes the gel getting faded, more thicker, increase of viscosity, adhesion and decrease of dispersive ability. Based on the physical properties test, (F2) with 3,5% concentration of Na-CMC is the optimal formula it caused by it suitable all the parameters of the physical properties of gel.